Implementation of Project Based Learning on Student Reasoning on Covid-19 Disaster Mitigation - Kiki Septaria; Binar Ayu Dewanti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
Disaster mitigation is activity that very important to teach and learning to someone as early as possible. Disaster mitigation can teach through positive activities such as school learning. This study aims to describe the implementation of Project Based Learning on students' reasoning for Class VII Covid-19 Disaster Mitigation at SMP 1 Maduran. This research is very much needed to see students' reasoning for understanding the concept of Covid-19 disaster mitigation and to train Covid-19 disaster preparedness as early as possible for students of SMPN 1 Maduran. The research method used One Group Pre-test Post-test Design with 30 students of grade VII at SMPN 1 Maduran. The results generally showed increase student reasoning with an average N-Gain score of 0.68 in the moderate category. The results of the increase in reasoning on each indicator, (1) namely explaining the relationship between the elements in the problem increased with an average N-Gain score of 0.58 in the moderate category, (2) made the problem solving project structure increase with an average N-Gain score of 0.76 with the High category, and (3) realizing projects that have been designed in the form of completion results increased with an average N-Gain score of 0.67 in the moderate category. Based on the data generated, it can be shown that learning using Project Based Learning is able to improve students' reasoning in class VII Covid-19 disaster mitigation material at SMPN 1 Maduran. Future research expected to be able measure students' creativity in the process of problems solving in mitigating the Covid-19 disaster.